2020
DOI: 10.1051/0004-6361/202039087
|View full text |Cite
|
Sign up to set email alerts
|

A novel framework for studying the impact of binding energy distributions on the chemistry of dust grains

Abstract: The evaporation of molecules from dust grains is crucial to understanding some key aspects of the star- and the planet-formation processes. During the heating phase, the presence of young protostellar objects induces molecules to evaporate from the dust surface into the gas phase, enhancing its chemical complexity. Similarly, in circumstellar discs, the position of the so-called snow lines is determined by evaporation, with important consequences for the formation of planets. The amount of molecules that are d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…However, the microphysics during the desorption involve the structure of the water ice and how the COMs reside in the ice matrix, requiring further understanding of how the chemical evolution takes place on the grain surface. Furthermore, the distribution of the binding energy can have a crucial effect on the estimate of the desorbed species (Ferrero et al 2020;Grassi et al 2020).…”
Section: Origin Of the Ch 3 Oh/ch 3 Cn Correlationmentioning
confidence: 99%
“…However, the microphysics during the desorption involve the structure of the water ice and how the COMs reside in the ice matrix, requiring further understanding of how the chemical evolution takes place on the grain surface. Furthermore, the distribution of the binding energy can have a crucial effect on the estimate of the desorbed species (Ferrero et al 2020;Grassi et al 2020).…”
Section: Origin Of the Ch 3 Oh/ch 3 Cn Correlationmentioning
confidence: 99%
“…The freeze-out of H 2 that occurs for high H 2 binding energies gives access to different parts of the reaction network, leading to a more methane-rich ice, instead of a methanol-rich ice that is found for lower binding energies. Grassi et al 158 found that the surface chemistry drastically changes when multiple binding sites are considered, instead of a single value binding site. They covered a range of different conditions, typical for the surroundings of a proto-star or in the disk mid-plane.…”
Section: Astrochemical Modelsmentioning
confidence: 99%
“…However, the microphysics during the desorption involve the structure of the water ice and how the COMs reside in the ice matrix, requiring further understanding of how the chemical evolution takes place on the grain surface. Also, the distribution of the binding energy can have crucial effect on the estimate of the desorbed species (Ferrero et al 2020;Grassi et al 2020).…”
Section: Origin Of the Ch 3 Oh/ch 3 Cn Correlationmentioning
confidence: 99%